Gambaran Pengetahuan Penanganan Keputihan pada Remaja Putri di Salah Satu SLTP Jember - Veronika Vestine (ARTERI : Jurnal Ilmu Kesehatan, 2019)
Adolescence is a period of individuals which shows the puberty changes until they reach the sexual maturity. While these changes occur due to an increase of hormonal levels, it causes the vaginal discharge in female adolescence. Vaginal discharge (leucorrhoea) affects about 50% of female population and approximately 75% of Indonesian women have experienced once in their life time. Both of physiological and pathological leucorrhea are a manifestation of uterine diseases symptoms. Leucorrhea can be treated and prevented by proper personal hygiene. The aim of this study is to describe the knowledge of female adolescence about leucorrhea management. The study was a descriptive quantitative with cross sectional approached. The samples were obtained from female students in junior high school grade VII and VIII. The 74 samples of female students were obtained by a total sampling technique. The 52% of early female adolescence and 55% of mid female adolescence have an adequate knowledge about leucorrhea management, whether 11% of early female adolescence and 9% of mid female adolescence have a good knowledge about leucorrhea management. The 45% respondents obtain the leucorrhea information from television. The lack information about leucorrhea or vaginal discharge can be solve by provide the good knowledge about prevention and administration itself.